Corporate Financial Strategy. - Bender, Ruth (Taylor and Francis, 2012)
Corporate Financial Strategy is a practical guide to understanding the elements of financial strategy, and how directors and advisors can add value by tailoring financial strategy to complement corporate strategy. The book sets out appropriate financial strategies over the key milestones in a company's life. It discusses the practicalities behind transactions such as:* Raising venture capital* Flotation on a stock exchange* Making acquisitions* Management buyouts* Financial restructuringIn explaining financing structures, the book sets out the basic building blocks of any financial instrument t.